1/Nc Expansion and Anomaly Cancellation in the Presence of Electroweak Interactions - Erdem, Recai; Erdem, Recai (IOP Publishing Ltd., 1998)
We study the question of a consistent formulation of the 1/Nc expansion in the presence of electroweak interactions. We show that in some cases the previous formulation leads to an unrealistic picture. We improve the scheme. We derive the corresponding hypercharge and electric charge values of fermions under the requirement that the standard model in the large-Nc limit should be free of chiral gauge anomalies. We find that the resulting hypercharge and the electric charge values for quarks are the same as for the standard model.
Keywords: Electroweak interactions; Baryons